Cucurbitacin E Induces Autophagy-Involved Apoptosis in Intestinal Epithelial Cells - Song, Huapei; Sui, Hehuan; Zhang, Qiong; Wang, Pei; Wang, Fengjun (Frontiers in Physiology, 2020)
Apoptosis plays a crucial role in maintaining the structural and functional integrity of the intestinal epithelial barrier. Autophagy mediates injury to and repair of the intestinal epithelial barrier through multiple pathways in pathophysiological conditions. Our earlier study has found that cucurbitacin E (CuE) regulates the proliferation, migration and permeability of human intestinal epithelial cells (IECs); however, its effects and mechanisms on apoptosis and autophagy are still unclear. This study reported that CuE induced apoptosis and promoted autophagy of IECs in a concentration-dependent manner. The results showed that CuE could inhibit the expression of apoptosis-related protein Bcl-2 and drove activation of caspase-3 and cleavage of its substrate poly (ADP-ribose) polymerase. CuE also facilitated the expression of endoplasmic reticulum stress-related proteins CHOP and Grp78 and autophagy-related proteins Beclin1 and LC3 while inhibiting the phosphorylation of AKT and mammalian target of rapamycin (mTOR). An autophagy inhibitor, 3-methyladenine, reduced CuE-induced apoptosis. These results suggest that CuE may induce apoptosis and autophagy in IECs via the PI3K/AKT/mTOR signalling pathway and that autophagy following endoplasmic reticulum stress participates in the pro-apoptotic process induced by CuE.